Urbanization and economic growth - Shukla, Vibhooti (Delhi Oxford University Press, 1996)
With special reference to India.
Keywords: Cities and towns -- Growth.%650 0 Rural-urban migration -- India -- India; Urbanization -- India; India -- Economic conditions -- 1947-.